Composite material modified diaphragm and negative-electrode-free sodium ion battery

By using composite materials to modify the separator in an anode-free sodium ion battery, combined with the addition of mesoporous molecular sieve and sodium salt, the problems of uneven distribution of sodium metals and dendrite are solved, and the separator performance and circulation capacity retention rate of the battery are significantly improved.

CN119542680APending Publication Date: 2025-02-28SHANDONG SACRED SUN POWER SOURCES
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411742747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

Smart Images

  • Figure BDA0005162894500000111
    Figure BDA0005162894500000111
  • Figure BDA0005162894500000121
    Figure BDA0005162894500000121
  • Figure HDA0005162894510000011
    Figure HDA0005162894510000011
Patent Text Reader

Abstract

The invention provides a composite material modified diaphragm, which comprises a base membrane and a composite material film compounded on the surface of the base membrane, and the raw materials of the composite material film comprise a binder, a mesoporous molecular sieve and a sodium salt. The invention also provides a sodium ion battery without a negative electrode. According to the composite material modified diaphragm provided by the invention, the raw materials comprise the mesoporous molecular sieve and the sodium salt, the mesoporous molecular sieve provides a diffusion path for directional transmission of sodium ions, the ionic conductivity of the composite material modified diaphragm is increased by the sodium salt, and meanwhile, the cycle performance of the sodium ion battery is improved by adding the mesoporous molecular sieve and the sodium salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a composite material modified diaphragm and a negative electrode-free sodium ion battery. Background Art

[0002] The scarcity of lithium resources has become the main problem restricting the development of lithium-ion batteries. As a new type of ion battery, sodium-ion batteries are characterized by abundant resources and low costs. They can be used as a supplement or substitute for lithium-ion batteries and have broad development prospects in the field of energy storage.

[0003] In the actual application of sodium-ion batteries, in order to ensure the reliability of sodium-ion batteries, the negative electrode is often excessive. This design reduces the energy density and initial efficiency of sodium-ion batteries, and the actual production process cannot meet the requirements of directly using metallic sodium as the negative electrode. Compared with lithium-ion batteries, the lower energy density of sodium-ion batteries limits their further application.

[0004] Anode-free sodium-ion batteries do not require anode materials and only require current collectors as electrodes, which can improve battery energy density and reduce battery costs. However, the side reactions caused by direct contact between the current collector and the electrolyte and the dendrite problem caused by the uneven precipitation of sodium metal on the surface of the current collector seriously affect the practical application of anode-free sodium-ion batteries. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a composite material modified diaphragm. The composite material modified diaphragm provided in the present application is applied to a sodium ion battery, and its diaphragm performance is significantly improved, and the sodium ion battery has a better cycle capacity retention rate.

[0006] In view of this, the present application provides a composite material modified diaphragm, including a base membrane and a composite material film composited on the surface of the base membrane, characterized in that the raw materials of the composite material film include a binder, a mesoporous molecular sieve and a sodium salt.

[0007] Preferably, the mass ratio of the binder to the mesoporous molecular sieve is 100:(1-20), and the mass ratio of the mesoporous molecular sieve to the sodium salt is 100:(1-10).

[0008] Preferably, the binder includes one or more of polyvinylidene fluoride, polyacrylamide, polymethyl methacrylate and polyvinyl acetate.

[0009] Preferably, the mesoporous molecular sieve includes one or more of MCM-41 molecular sieve, SBA-15 molecular sieve and KIT-6 molecular sieve.

[0010] Preferably, the sodium salt comprises one or more of NaPF6, NaOTF, NaFSI and NaTFSI.

[0011] Preferably, the base film comprises one of PP, PE, PI, PET and cellulose base films.

[0012] Preferably, the method for preparing the composite material modified diaphragm specifically comprises the following steps:

[0013] S1) mixing a binder and a solvent to obtain a first slurry, and mixing the mesoporous molecular sieve and the first slurry to obtain a second slurry;

[0014] S2) mixing the sodium salt and the second slurry to obtain a third slurry;

[0015] S3) forming the third slurry on the surface of the base film, and obtaining a composite material modified diaphragm after drying.

[0016] Preferably, in the first slurry, the mass ratio of the binder to the solvent is 1:(15-20); and the drying temperature is 40-100°C.

[0017] The present application also provides a negative electrode-free sodium ion battery, comprising the composite material modified diaphragm.

[0018] Preferably, the composite material layer of the composite material modified film layer is in contact with the negative electrode current collector and is bonded by hot pressing; the sodium ion battery includes an aqueous sodium ion battery, an organic sodium ion battery, and a sodium-sulfur battery.

[0019] The present application provides a composite material modified diaphragm, which includes a base film and a composite material film composited on the surface of the base film, wherein the raw materials of the composite material film include a binder, a mesoporous molecular sieve and a sodium salt; the addition of the sodium salt in the composite material film is beneficial to improving the ionic conductivity of the composite film, and the mesoporous molecular sieve can even out the sodium ion flux, thereby inhibiting the generation of sodium dendrites; at the same time, the combined addition of the two achieves a synergistic effect, and ultimately the air permeability, puncture strength, tensile strength and ionic conductivity of the obtained composite material modified diaphragm are improved, and the impedance is reduced, thereby ensuring the diaphragm performance of the composite material diaphragm, and having a good cycle capacity retention rate; further, the composite material modified diaphragm provided in the present application is directly bonded to the current collector after hot pressing, thereby avoiding direct contact between the electrolyte and the current collector and reducing the occurrence of side reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flow chart of the preparation of the composite material modified diaphragm provided by the present invention;

[0021] Figure 2 A schematic diagram of the structure of a composite material modified diaphragm provided by the present invention;

[0022] Figure 3ion conductivity curves of the diaphragms used in the embodiments of the present invention and the comparative examples;

[0023] Figure 4 The 0.2C cycle capacity retention rate curve of the sodium ion battery provided in the embodiments and comparative examples is shown. DETAILED DESCRIPTION

[0024] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0025] In view of the problem of uneven distribution of sodium metal in a negative electrode-free sodium ion battery in the prior art, which in turn affects the performance of the sodium ion battery, the present invention is based on further research and development and innovation of the diaphragm to prepare a composite material modified diaphragm, the introduction of sodium salt can improve its own ion conductivity, and the evenly distributed mesoporous molecular sieve can evenly distribute the flux of sodium ions to inhibit the generation of sodium dendrites, thereby improving the cycle life of the negative electrode-free sodium ion battery; further, the composite material modified diaphragm can be bonded to the negative electrode collector by hot pressing, avoiding direct contact between the electrolyte and the collector, and improving the electrochemical performance of the sodium ion battery; specifically, an embodiment of the present invention discloses a composite material modified diaphragm, including a base film and a composite material film composited on the surface of the base film, the raw materials of the composite material film including a binder, a mesoporous molecular sieve and a sodium salt.

[0026] In the composite material modified diaphragm provided in the present application, the base film is well known to those skilled in the art. For example, the base film includes one of PP, PE, PI, PET and cellulose base films.

[0027] In the composite film, the binder is specifically selected from one or more of polyvinylidene fluoride, polyacrylamide, polymethyl methacrylate and polyvinyl acetate; the mesoporous molecular sieve is selected from one or more of MCM-41 molecular sieve, SBA-15 molecular sieve and KIT-6 molecular sieve; the application has no particular restrictions on the sources of the binder and the mesoporous molecular sieve, which can be commercially available products. The sodium salt includes one or more of NaPF6, NaOTF, NaFSI and NaTFSI. The mass ratio of the binder to the mesoporous molecular sieve is 100:(1-20). Specifically, the mass ratio of the binder to the mesoporous molecular sieve is 100:(3-15). For example, the mass ratio of the binder to the mesoporous molecular sieve in the present application is 100:2, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15, 100:16, 100:17, 100:18, and 100:19. The mass ratio of the mesoporous molecular sieve and the sodium salt is 100:(1-10), specifically, the mass ratio of the mesoporous molecular sieve and the sodium salt is 100:(2-8); for example, the mass ratio of the mesoporous molecular sieve and the sodium salt in the present application is 100:3, 100:4, 100:5, 100:6, 100:7, 100:9; the mass ratio of the mesoporous molecular sieve and the sodium salt will affect the properties of the diaphragm itself, and will also affect the cycle performance of the sodium ion battery.

[0028] The preparation method of the composite modified diaphragm described in the present application specifically comprises the following steps:

[0029] S1) mixing a binder and a solvent to obtain a first slurry, and mixing the mesoporous molecular sieve and the first slurry to obtain a second slurry;

[0030] S2) mixing the sodium salt and the second slurry to obtain a third slurry;

[0031] S3) forming the third slurry on the surface of the base film, and obtaining a composite material modified diaphragm after drying.

[0032] In the preparation process of the composite modified diaphragm, in order to ensure the uniform distribution of the mesoporous molecular sieve, the binder, the mesoporous molecular sieve and the sodium salt are sequentially added to the slurry; first, the binder and the solvent are mixed to obtain the first slurry, and the solvent is a solvent well known to those skilled in the art, and for example, the solvent is selected from NMP; in the first slurry, the mass ratio of the binder to the solvent is 1: (15-20), more specifically, the mass ratio of the binder to the solvent is 1: (16-19); the drying temperature is 40-100°C, specifically, the drying temperature is 50-80°C, and more specifically, the drying temperature is 60-70°C. In the present application, the third slurry is formed on a single side of the base film, and the formation method is exemplified by spraying; after drying, a single side of the base film is compounded with a composite thin film.

[0033] The present application also provides a negative electrode-free sodium ion battery, which includes a composite material modified diaphragm as described in the above scheme.

[0034] For a sodium ion battery without a negative electrode, it is obtained by hot pressing a positive electrode sheet, a negative electrode sheet and a composite material modified diaphragm, and the composite material film of the composite material modified diaphragm is in contact with the current collector of the negative electrode sheet; the positive electrode sheet and the negative electrode sheet are well known to those skilled in the art, and this application does not impose any special restrictions on this.

[0035] In the present application, the sodium ion battery includes an aqueous sodium ion battery, an organic sodium ion battery or a sodium-sulfur battery.

[0036] The present invention provides a composite material modified diaphragm, wherein the addition of sodium salt can increase the ionic conductivity of the composite film, and the evenly distributed mesoporous molecular sieve can evenly distribute the flux of sodium ions, thereby inhibiting the generation of sodium dendrites; further, the composite material modified diaphragm is bonded to a current collector after hot pressing, thereby avoiding direct contact between an electrolyte and the current collector, thereby reducing the generation of side reactions; the composite material modified diaphragm provided by the present invention has a simple and controllable preparation process, strong homogenization, and simple materials used, and is more suitable for industrial applications.

[0037] In order to further understand the present invention, the composite material diaphragm provided by the present invention is described in detail below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0038] Example 1 A method for preparing a composite material-modified diaphragm and a negative electrode-free sodium ion battery

[0039] The specific steps include:

[0040] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0041] (2) mixing the binder and the solvent evenly, adding the mesoporous molecular sieve thereto and continuing to stir, and then adding the sodium salt thereto and mixing evenly to prepare a composite material slurry; wherein the binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is a commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10; the selected sodium salt includes NaPF6; the mass ratio of the selected mesoporous molecular sieve and the sodium salt is 100:8;

[0042] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0043] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0044] Example 2 Preparation method of a composite material modified diaphragm and a negative electrode-free sodium ion battery

[0045] The specific steps include:

[0046] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0047] (2) mixing the binder and the solvent evenly, adding the mesoporous molecular sieve thereto and continuing to stir, and then adding the sodium salt thereto and mixing evenly to prepare a composite material slurry; wherein the binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is a commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10; the selected sodium salt includes NaPF6; the mass ratio of the selected mesoporous molecular sieve and the sodium salt is 100:5;

[0048] (3) coating the uniformly mixed slurry onto a PP base film, wherein the thickness of the PP base film is 12 μm and the coating thickness is 10 μm, and forming a composite film-modified diaphragm after drying, and the drying temperature is 70° C.;

[0049] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0050] Example 3 Preparation method of a composite material modified diaphragm and a negative electrode-free sodium ion battery

[0051] The specific steps include:

[0052] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0053] (2) mixing the binder and the solvent evenly, adding the mesoporous molecular sieve thereto and continuing to stir, and then adding the sodium salt thereto and mixing evenly to prepare a composite material slurry; wherein the binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is a commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10; the selected sodium salt includes NaPF6; the mass ratio of the selected mesoporous molecular sieve and the sodium salt is 100:2;

[0054] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0055] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0056] Comparative Example 1

[0057] The specific steps include:

[0058] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0059] (2) The binder and the solvent are mixed evenly, and then the mesoporous molecular sieve is added thereto and stirred continuously, and then the sodium salt is added thereto and mixed evenly to form a composite material slurry; the selected binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is the commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10; the selected sodium salt is NaPF6; the mass ratio of the selected mesoporous molecular sieve and the sodium salt is 100:30;

[0060] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0061] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0062] Comparative Example 2

[0063] The specific steps include:

[0064] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0065] (2) The binder and the solvent are mixed evenly, and then the mesoporous molecular sieve is added thereto and stirred continuously, and then the sodium salt is added thereto and mixed evenly to form a composite material slurry; the selected binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is the commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10; the selected sodium salt is NaPF6; the mass ratio of the selected mesoporous molecular sieve and the sodium salt is 100:0.5;

[0066] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0067] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0068] Comparative Example 3

[0069] The specific steps include:

[0070] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0071] (2) mixing the binder and the solvent evenly, adding the mesoporous molecular sieve thereto and continuing to stir, and mixing evenly to form a composite material slurry; the selected binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected molecular sieve material is a commercial SBA-15 molecular sieve; the mass ratio of the selected binder and the mesoporous molecular sieve is 100:10;

[0072] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0073] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0074] Comparative Example 4

[0075] The specific steps include:

[0076] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd.-XN33S) was stirred and mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, with the mass ratio of positive electrode material: conductive carbon: PVDF being 90:5:5. After stirring evenly, the mixture was coated on aluminum foil and vacuum dried to obtain a positive electrode sheet;

[0077] (2) The binder and the solvent are mixed evenly, and then the sodium salt is added thereto and mixed evenly to form a composite material slurry; the selected binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, and the mass ratio of PVDF:NMP is 5:95; the selected sodium salt is NaPF6; the mass ratio of the selected binder and the sodium salt is 100:0.5, which is consistent with the mass ratio of the binder and the sodium salt used in Example 2;

[0078] (3) coating the composite material slurry onto a PP base film, wherein the thickness of the PP base film is 16 μm and the coating thickness is 10 μm, and after drying, a composite material film modified diaphragm is formed, and the drying temperature is 70° C.;

[0079] (4) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and composite material modified diaphragm are assembled. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. Hot pressing is performed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0080] Comparative Example 5

[0081] The specific steps include:

[0082] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd. - XN33S) was mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, and the mixture was evenly stirred and coated on an aluminum foil, and then vacuum dried to obtain a positive electrode sheet;

[0083] (2) mixing the binder and the solvent evenly and coating them on the PP base film, wherein the selected binder is polyvinylidene fluoride (PVDF), the selected solvent is NMP, the mass ratio of PVDF:NMP is 5:95, the thickness of the PP base film is 16 μm, the coating thickness is 10 μm, and after drying, a PVDF-coated diaphragm is formed, and the drying temperature is 70°C;

[0084] (3) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-side carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and PVDF-coated diaphragm are used for assembly. During assembly, the side of the diaphragm coated with the modified layer faces the negative electrode current collector. The battery is hot-pressed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0085] Comparative Example 6

[0086] The specific steps include:

[0087] (1) A commercial sodium nickel iron manganese oxide positive electrode material (Jiangsu Xiangying New Energy Technology Co., Ltd. - XN33S) was mixed with conductive carbon, and then a PVDF solution with NMP as a solvent was added, and the mixture was evenly stirred and coated on an aluminum foil, and then vacuum dried to obtain a positive electrode sheet;

[0088] (2) The sodium nickel iron manganese oxide electrode prepared in step (1) is used as the positive electrode and the carbon-coated aluminum foil is used as the negative electrode. The carbon-coated aluminum foil is carbon-coated on both sides, the base foil thickness is 12 μm, and the single-sided carbon coating layer thickness is 1 μm. The prepared positive electrode sheet, negative electrode sheet, and uncoated PP diaphragm are used for assembly. The thickness of the PP diaphragm is 16 μm. The battery is hot-pressed at 80° C. and 2T for 40 s. The assembled battery is injected with liquid and subjected to cycle performance tests. The cycle operating voltage is 2.0-3.95 V and the rate is 0.2C.

[0089] Figure 1 The following is a flow chart for preparing composite material modified diaphragm. It is recommended to prepare composite slurry according to this process. The preparation process of this method is simple and controllable, with strong homogeneity, simple materials used, and more suitable for industrial application.

[0090] Figure 2 This is a schematic diagram of the structure of a composite material modified diaphragm, as shown in the figure, wherein 1 is a base membrane in the lower layer, 2 is a composite material coated on the upper layer of the base membrane, and when assembling the battery, the side coated with the composite material faces the negative electrode.

[0091] Figure 3 The ionic conductivity curves of the membranes used in the examples and comparative examples are shown in FIG.

[0092] Table 1 is a table of performance test results of the diaphragms prepared in the examples and comparative examples. Table 1 is a table of performance comparison of the diaphragms prepared in the examples and comparative examples.

[0093]

[0094]

[0095] It can be seen from Table 1 that after the base membrane is modified with the composite material, its porosity, air permeability, puncture strength and tensile strength are all improved, and the ionic conductivity is reduced, and the performance of the modified membrane is significantly improved; the ratio of mesoporous molecular sieve and sodium salt directly affects the performance of the modified membrane. The addition of mesoporous molecular sieve has a greater effect on the porosity and air permeability of the membrane, and the addition of sodium salt has a greater effect on the ionic conductivity of the membrane.

[0096] Table 2 Comparison of 0.2C cycle performance of each embodiment and comparative example

[0097] Serial number Cathode Materials Number of cycles Capacity retention rate / % Example 1 Nickel iron sodium manganate 100 83.4 Example 2 Nickel iron sodium manganate 100 82.2 Example 3 Nickel iron sodium manganate 100 83.2 Comparative Example 1 Nickel iron sodium manganate 100 73.3 Comparative Example 2 Nickel iron sodium manganate 100 72.4 Comparative Example 3 Nickel iron sodium manganate 100 72.1 Comparative Example 4 Nickel iron sodium manganate 100 59.8 Comparative Example 5 Nickel iron sodium manganate 100 61.2 Comparative Example 6 Nickel iron sodium manganate 100 57.3

[0098] Figure 4 The 0.2C cycle capacity retention rate curve of the battery of the embodiment and the comparative example; Figure 4As can be seen from Table 2, the cycle performance of Examples 1-3 and Comparative Examples 1-2 is significantly better than that of Comparative Examples 3-6, indicating that the combination of mesoporous molecular sieve and sodium salt has a significant improvement in the performance of the battery, and the performance improvement is greater than that of the modification methods of adding mesoporous molecular sieve alone or adding sodium salt alone, that is, the diaphragm modified with a composite material of mesoporous molecular sieve and sodium salt is more effective in improving the battery cycle performance; the cycle performance of Examples 1-3 is significantly better than that of Comparative Examples 1-4, indicating that different addition ratios of mesoporous molecular sieve and sodium salt have an impact on the improvement of battery cycle performance, and the appropriate addition ratio has the most obvious improvement on battery performance.

[0099] In summary, the composite material modified diaphragm provided by the present application increases the ionic conductivity of the composite film by adding sodium salt to the composite material, and the added uniformly distributed mesoporous molecular sieve can even out the flux of sodium ions to inhibit the generation of sodium dendrites. The diaphragm coated with the film is bonded to the current collector after hot pressing, avoiding direct contact between the electrolyte and the current collector to reduce the generation of side reactions. The preparation process of the present invention is simple and controllable, with strong homogenization, simple materials used, and more suitable for industrial applications; the composite diaphragm structure design of the present application has great application prospects for negative electrode-free sodium metal batteries.

[0100] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0101] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite material modified diaphragm, comprising a base film and a composite material film composited on the surface of the base film, characterized in that: The raw materials of the composite material film include a binder, a mesoporous molecular sieve and a sodium salt.

2. The diaphragm according to claim 1, characterized in that The mass ratio of the binder to the mesoporous molecular sieve is 100:(1-20), and the mass ratio of the mesoporous molecular sieve to the sodium salt is 100:(1-10).

3. The diaphragm according to claim 1, characterized in that The binder includes one or more of polyvinylidene fluoride, polyacrylamide, polymethyl methacrylate and polyvinyl acetate.

4. The diaphragm according to claim 1, characterized in that The mesoporous molecular sieve includes one or more of MCM-41 molecular sieve, SBA-15 molecular sieve and KIT-6 molecular sieve.

5. The diaphragm according to claim 1, characterized in that The sodium salt includes one or more of NaPF6, NaOTF, NaFSI and NaTFSI.

6. The diaphragm according to claim 1, characterized in that The base film includes one of PP, PE, PI, PET and cellulose base films.

7. The diaphragm according to claim 1, characterized in that The preparation method of the composite material modified diaphragm specifically comprises the following steps: S1) mixing a binder and a solvent to obtain a first slurry, and mixing the mesoporous molecular sieve and the first slurry to obtain a second slurry; S2) mixing the sodium salt and the second slurry to obtain a third slurry; S3) forming the third slurry on the surface of the base film, and obtaining a composite material modified diaphragm after drying.

8. The diaphragm according to claim 7, characterized in that In the first slurry, the mass ratio of the binder to the solvent is 1:(15-20); and the drying temperature is 40-100°C.

9. A negative electrode-free sodium ion battery, comprising a composite material modified diaphragm according to any one of claims 1 to 8.

10. The negative electrode-free sodium ion battery according to claim 9, characterized in that: The composite material layer of the composite material modified film layer is in contact with the negative electrode current collector and is bonded by hot pressing; the sodium ion battery includes an aqueous sodium ion battery, an organic sodium ion battery, and a sodium-sulfur battery.

Citation Information

Cited By

  • Design method of high-entropy MXene-high-viscosity colloid composite coating battery diaphragm

    CN120300403A

  • Design method for high-entropy MXene-high-viscosity colloid composite coating battery separator

    CN120300403B

  • Negative-electrode-free sodium ion battery current collector, preparation method and application thereof, and negative-electrode-free sodium ion battery

    CN120545369A